Determination of Some Changes in Chemical, Physical and Sensory Properties of Kebab when admixed with Chicken Breast Meat - Ali, Bana Azad Mohamed; Hassan, Khulod Ibraheem; Mohammed, Naska Abdulkadir (Sulaimani Journal for Pure and Applied Sciences, 2018)
The objective of this research was to determine chemical composition, physiochemical and sensory traits of kababafter adding chicken breast meat with different concentrations. The standard mixture of kebab considered as control treatment (20% beef, 5% sheep fat tail and 75% meat of sheep flank) was treated with addition of different concentrations of chicken breast meat (the concentration of meat from sheep flank area was changed by lowering from 75% to 45%) as T1, T2, T3, T4, T5 in rate of 10%, 15%, 20%, 25%, 30%, respectively. After preparing the samples, sensory evaluation was conducted for all of the kebab treatments. This wasfollowed by chemical analysis measurements for the raw and grilled samples, which comprised of the several parameters including the percentage of moisture, protein, fat and ash contents. Studying of the changes in the organoleptic features laterwas represented by measuring pH, peroxide value; free fatty acid (Acid Value), beside cholesterol content and water holding capacity. Overall, moisture content, similar to protein, increased when chicken meat was added. Whereas fat and water holding capacity (W.H.C) decreased. However, no significant difference was observed in changes of ash content among treatments. As regard meat fat parameters which includes peroxide value, free fatty acid and cholesterol, their values decreased significantly in samples where chicken meat was added. For the sensory evaluation, in general, significant lower values were obtained for treatments contained the highest concentration of chicken breast meat.
Keywords: kebab; chicken breast